Effects of design consistency on run-off-road crashes: An application of a Random Parameters Negative Binomial Lindley model. (June 2023) - Khan, Shinthia Azmeri; Afghari, Amir Pooyan; Yasmin, Shamsunnahar; Haque, Md Mazharul
Highlights: Geometric design consistency of two-lane rural highways is correlated with run-off-road crashes. Three design consistency measures are alignment consistency, operating speed consistency and driving dynamics consistency. Multiple road geometric characteristics captured through design consistency are critical for run-off-road crashes. Sudden changes in roadway alignment increase the risk of run-off-road crashes. High variations in operating speed are associated with run-off-road crash risks. Abstract: Run-off-road crashes are one of the most common crash types, especially in rural roadway environments contributing significantly to fatalities and severe injuries. These crashes are complex and multi-dimensional events, and factors like road geometry, driver behaviour, traffic characteristics and roadside features contribute to their occurrence, separately or interactively. Sudden changes in road geometry, in particular, can influence driver behaviour, and therefore, in developing a micro-level crash risk model for run-off-road crashes, one of the challenges is incorporating the effects of driver behaviour (disaggregated information) that may arise from the variations in road geometry (aggregated information). This study aims to examine the interaction between road geometry and driver behaviour through a set of measures for design consistency on two-lane rural roads. Multiple data sources, including crash data for 2014–18, traffic data, probe speed data and roadway geometric data, for twenty-three highways in Queensland, Australia, have been fused for this study. Seventeen types of design consistency measures with regard to alignment consistency, operating speed consistency and driving dynamics are tested. A run-off-road crash risk model is estimated by employing the Random Parameters Negative Binomial Lindley regression framework, which accounts for excess zeros in the crash counts and captures the effects of unobserved heterogeneity in the parameter estimates. Results indicate that the geometric design consistency capturing the interaction between driver behaviour and operational factors better predicts run-off-road crashes along rural highways. In addition, roadside attributes like clear zone width, infrastructures, terrain, and roadway remoteness also contribute to run-off-road crashes. The findings of the study provide a comprehensive understanding of the influence of variations in roadway geometry on driver behaviour and run-off-road crashes along rural highways.